Bu Kasur Totalitasnya Dalam Dunia Anak - Datti, Vegaisyah Mutia; Humaidi, Humaidi; Martini, Sri (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
This study aims to explain the role of Mother Mattress in the world of children. Mrs. Kasur or with the real name Sandiah is one of the Indonesian education leaders who is active in children”s education. Mrs. Kasur”s journey began when she followed in her husband”s footsteps as a host and nanny at RRI Garut in 1947. Mrs. Kasur followed in her husband”s footsteps because she was interested in the education of Indonesian children who were still underdeveloped. It was this problem that made Mrs. Kasur and her husband start dedicating themselves to Indonesian children”s education by creating children”s songs, filling in children”s stories, and conducting social activities about children. One of the famous and legendary songs written by Mrs. Kasur, namely